Characteristics and dynamics of two major Greenland glacial fjords. Issue 6 (16th June 2014) - Sutherland, David A.; Straneo, Fiammetta; Pickart, Robert S.
Key Points We describe fjord and shelf circulation patterns in two large glacial fjords Time‐dependent, externally driven intermediary circulation dominates both fjords We charactertize these fjords in estuarine parameter space